2003
DOI: 10.1301/nr.2003.janr.1-33
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones: a Safety Review

Abstract: Soy isoflavones have been a component of the diet of certain populations for centuries. The consumption of soy generally has been considered beneficial, with a potentially protective effect against a number of chronic diseases; because of their estrogenic activity, however, negative effects of isoflavones have been postulated. This review examines the literature associated with the safety of soy isoflavones, including dietary soy isoflavone exposure data of populations with high soy intakes, human studies in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(150 citation statements)
references
References 161 publications
(233 reference statements)
0
130
0
9
Order By: Relevance
“…A review by Munro and colleagues 52 concluded that the literature, when viewed in its entirety, supports the notion that soy isoflavones consumed in foods or dietary supplements are safe. The report by Unfer and associates, 53 however, has raised questions of safety with regard to long-term use of higher doses of soy isoflavones.…”
Section: Safetymentioning
confidence: 97%
“…A review by Munro and colleagues 52 concluded that the literature, when viewed in its entirety, supports the notion that soy isoflavones consumed in foods or dietary supplements are safe. The report by Unfer and associates, 53 however, has raised questions of safety with regard to long-term use of higher doses of soy isoflavones.…”
Section: Safetymentioning
confidence: 97%
“…These reports indicate that maternal GEN can cross the placenta and affect the central nervous system (CNS) of fetuses. Furthermore, the absorption and elimination of soy isoflavones in infants differs from adults since intestinal bacterial flora remains undeveloped in infants [10]. Due to the high exposure of soy in some fetuses and infants, it is important to define the effects of GEN on perinatal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…La evaluación de la seguridad que representa el consumo de las ISO ha sido comprendida por diversas agencias gubernamentales y no gubernamentales de Europa, Estados Unidos de Norteamérica y Japón. Los estudios tanto epidemiológicos como clínicos en humanos apoyan el planteamiento que las ISO son seguras 29 . Algunos trabajos, en animales de experimentación y con células en cultivo, sin embargo, indican que los productos que contienen ISO podrían representar un peligro para las mujeres con alto riesgo de desarrollar cáncer de mama.…”
Section: Pubertadunclassified